Influencia del baile en el desarrollo psicomotor y socioemocional en niños de educación inicial - Ortiz Andrade, Elena Marisol (2025)
The study identified the influence of dance on the psychomotor and socio-emotional development of children in early education through a review of the literature; the benefits of dance in improving gross and fine motor skills, and its impact on coordination, body control and spatial perception were considered. The results showed that dance promotes physical development and socio-emotional skills such as communication, cooperation and emotional regulation, which allow long-term academic and social success. However, in Ecuador, the implementation of dance as a pedagogical strategy is limited, as the positive results shown in international studies are not obtained. The importance of defining educational policies that promote the integration of dance in the school curriculum is emphasized and the need to provide training to teachers and provide the necessary resources to implement this pedagogical tool effectively is highlighted. Dance, through its characteristics, can contribute to the comprehensive development of children, especially invulnerable contexts where access to educational programs is limited, but investment in infrastructure and teacher training is required to ensure that children, regardless of their environment, can take advantage of the benefitsthat dance offers in their psychomotor and socio-emotional development.